HEDGING DEVICES IN INTERPRETING RESEARCH DATA: A STUDY IN STUDENTS’ UNDERGRADUATE THESIS - Faksi Rana Al-Kahfi; Kurniawan Apgrianto; Ahmad Junaidi (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aims at describing the use of hedging devices found in interpreting research data in finding and discussion section of students’ undergraduate thesis. It is focused on describing its types, functions and meaning used in finding and discussion section. In the data collection, the data was gathered by using descriptive qualitative method. The source of this research was taken from the statements and claims written in finding and discussion section of students’ undergraduate theses. The result of the data analysis showed that the most frequently used type and function of hedging was Approximator of Degree, Frequency, Time and Quantity and Attribute Hedge. It is caused that most of the writers often state a speculation, assumption, opinion or probability through their statement in which decreases the explicitness of a statement and hence enables the writer to be less direct and bald in communicating his/her meaning. It is also the signal that what they state is not completely true.